If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + -2s = sinx * cosy Multiply insx * cosy r + -2s = cinos2xy Solving r + -2s = cinos2xy Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '2s' to each side of the equation. r + -2s + 2s = cinos2xy + 2s Combine like terms: -2s + 2s = 0 r + 0 = cinos2xy + 2s r = cinos2xy + 2s Simplifying r = cinos2xy + 2s
| 3m+5=8m+105 | | 3m+5=8m-1-5 | | 4+3n=n-7+n | | 3+5m=8m-105 | | 3x+5=3(2x+4)+3x | | -79+x+9x=41 | | .04x+.2(6-x)=.08(6) | | -3(4t-2)+5t=6t-8 | | D=5d-6 | | 1=.5x*3.61 | | 8+2(3x-2)=5 | | -1(n*n+3)=2(-4*3) | | 240=128t-16t^2 | | 1/2x-1/5=-10 | | 2(0.36x+11d)= | | -5(x+3)-8=-23 | | p=0.007*4600 | | -x+2x-12=5 | | 16x-1y= | | -1(3*3)=2(-4*3) | | 23x-5+21x+5=23x-5+21x+5s | | 15=-3(n-2)-6 | | y+8=-5(x-3) | | X(2+9x)=0 | | 6m-4=7m+7-m | | -8(9x+9)+6= | | 15-(4v+4)=-4v-11 | | 5x+x+60=90 | | 6+(3+b)= | | 4(4-2x)=24-4x | | 5x+2y+2=80 | | 2*2-18x=0 |